Deceptive promises: women's understandings of technology in maternity care - STACH, MALGORZATA (Trinity College Dublin. School of Nursing & Midwifery. Discipline of Nursing, 2020)
The biomedical approach of obstetrics, relying on intensive use of technologies, has been championed as the most relevant approach to women's needs in childbirth, and to problems faced by maternity services in Ireland, and internationally. Despite the attempts to humanise care and produce evidence to encourage the appropriate use of birth technologies, most changes within this existing paradigm have been superficial or unsuccessful. As a result the rates of technological intervention into birth process, such as caesarean section, induction of labour, fetal monitoring and epidural analgesia, and 'active' management of labour, have been increasing sharply. Surprisingly, women's conceptualisations of technology, given such profound technologisation, have been relatively unexplored in the literature and their voices have been marginalised or disregarded in public debates and health policy. This study explores women's conceptualisations of technology in a highly technologised context of maternity services in Ireland in order to reimagine our understanding of technology and its effects in maternity care. The study used feminist poststructuralism as its theoretical framework and employed Foucauldian discourse analysis as its methodological stance. Women's understandings were generated using photo-elicitation interviews with photographs of hospital environments and of women being cared for within those environments. My analysis is based on twenty-one individual and three group interviews, with twenty-nine participants overall. Women from across social and cultural backgrounds who experienced different types of care within the Irish maternity services participated. The accounts of two men were also included. While feminist poststructuralism was used to theorise the ambivalence and conflicts in women's understanding and emphasise their marginalised knowledges, discourse analysis allowed to capture the powerful discourses which shape women's conceptualisations, and to grasp how they assemble their understanding of technology from available discursive resources. The findings of this study reveal the ambiguity and conflicts in women's understanding of technology in maternity care, and the discrepancies between their voices and the discourse of technocratic biomedicine. The capabilities of technology used within the obstetric approach offer women a limited notion of care, yet such care is often considered clinically faultless. Instead, women insist on the humane rather than technological imperatives as essential in ensuring care which is genuinely enabling and facilitative of their needs. Women's voices challenge the persuasive strategies of biomedicine and expose its promises as deceptive, giving only the appearance of comprehensive maternity care. Women's voices suggest an urgent need to shift the model towards the midwifery approach to ensure appropriate use of technology in maternity care and appropriate maternity services.
APPROVED
Keywords: technology in maternity care; women's voices; midwifery; obstetrics; discourse analysis; feminist poststructuralism; photo-elicitation; maternity services; appropriate technology; maternity services